2001
DOI: 10.1076/jcen.23.5.662.1238
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary and Automatic Visual Spatial Shifts of Attention in Parkinsons Disease: An Analysis of Costs and Benefits

Abstract: Visual spatial shifts of attention were investigated in 13 patients suffering from Parkinson's disease and 20 control subjects. Attention was directed towards a target location with peripheral or central cues at varying SOAs in two separate experiments. A benefit and cost analysis was conducted on reaction times. The results of the central cueing task showed that in comparison with control subjects, costs of invalid cueing were reduced in patients. Results of the peripheral cueing task revealed that although t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
2
12
1
1
Order By: Relevance
“…While patients' braking points showed a significant advantage in response to Valid Cues relative to Invalid Cues, controls were found to brake similarly during Valid and Invalid Cueing conditions. This result contrasts to findings of studies using central cueing paradigms that reported similar effects of Valid Cueing relative to Invalid Cueing on task performance of patients and age-matched controls [41] and may simply reflect the relatively low demands of the driving task which did not sufficiently challenge the control participants. Interestingly, results further indicated that, compared with the No Cue condition, Invalid Cues did not incur any significant response cost to braking point for either group.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…While patients' braking points showed a significant advantage in response to Valid Cues relative to Invalid Cues, controls were found to brake similarly during Valid and Invalid Cueing conditions. This result contrasts to findings of studies using central cueing paradigms that reported similar effects of Valid Cueing relative to Invalid Cueing on task performance of patients and age-matched controls [41] and may simply reflect the relatively low demands of the driving task which did not sufficiently challenge the control participants. Interestingly, results further indicated that, compared with the No Cue condition, Invalid Cues did not incur any significant response cost to braking point for either group.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with this prediction, patients benefitted to a significantly greater extent (20.91 m gain in brake point) than controls (10.86 m gain) from the provision of Valid Cues relative to noncued conditions. This finding is also consistent with results from peripheral cueing tasks that report greater effects of Valid cueing for patients compared with controls [41]. …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Numerous studies have identified altered spatial attention in PD (Filoteo et al, 1997; Filoteo et al, 2002; Pollux & Robertson, 2001; Wylie & Stout, 2002; Wright, Burns, Geffen, & Geffen, 1990; Yamaguchi & Kobayashi, 1998; but see Hsieh, Lee, Hwang, & Tsai, 1997), whereas other studies suggest that these patients are unimpaired on some purely object-based attentional tasks (Lee, Wild, Hollnagel, & Grafman, 1999; Possin, Cagigas, Strayer, & Filoteo, 2006). These past studies suggest that PD patients’ deficit in the spatial condition may be related to attentional deficits.…”
Section: Discussionmentioning
confidence: 99%
“…Apresentam um nível de atenção maior que o normal para a realização de atividades motoras, sejam estas atividades automáticas previamente aprendidas ou programas motores novos; e a divisão da atenção em mais de uma tarefa, por aumentar a pressão nas reservas atencionais, prejudica o desempenho motor dos pacientes principalmente no equilíbrio e marcha (SHARPE, 1992), podendo gerar risco de quedas (LUNDIN-OLSSON, NYBERG, GUSTAFSON, 1997). Além do enfoque clínico, alguns trabalhos na literatura abordam os déficits de gerenciamento atencional na DP sob um enfoque experimental (WRIGHT et al, 1990;SHARPE, 1992, ROWE et al, 2002, STAM et al, 1993POLLUX;ROBERTSON, 2001;JONES, 1994). A maioria deles utiliza como base o chamado "Paradigma de Posner", no qual os sujeitos são orientados a responder o mais rápido possível a um estímulo, que pode ser apresentado como esperado (condição válida), igualmente provável (condição neutra) ou inesperado (condição inválida) no campo visual.…”
Section: Sintomas Não Motoresunclassified